PENGUATAN MOTIVASI BELAJAR SISWA MELALUI PENERAPAN VIDEO BASED-LEARNING PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI KELAS X MADRASAH ALIYAH YAA BUNAYYA - Kumala Sari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low interest in learning and the emergence of acute boredom among students when analyzing theoretical-textual chronological narratives underlie this research. These operational issues trigger the passivity of tenth-grade students in internalizing the value of historical role models in the History of Islamic Culture subject. The main focus of this scientific study is to explore strengthening student learning motivation through the application of video-based learning methods. The steps of this descriptive qualitative research were operated through purposive sampling of informants involving the madrasah principal, subject teachers, and twelve active students. The primary field data collection procedure was collected through in-depth interviews, participatory observation, and documentation studies, which were then analyzed through an interactive model including data reduction, presentation, and drawing conclusions. The research findings indicate that the integration of audiovisual media is able to transform the classroom atmosphere to be more dynamic, inclusive, and responsive. The visualization of historical facts has proven to be reliable in converting abstract material into concrete material to stimulate students' attention and self-confidence. The main conclusion confirms that this instructional digitalization is very effective in minimizing cognitive barriers despite still being hampered by limited projector and loudspeaker facilities. Madrasah practitioners are recommended to consistently improve their digital pedagogical competencies as a whole. ABSTRAK Rendahnya minat belajar serta munculnya kejenuhan akut siswa saat menelaah narasi kronologis yang bersifat teoretis-tekstual melatarbelakangi penelitian ini. Masalah operasional tersebut memicu kepasifan siswa kelas sepuluh dalam menghayati nilai keteladanan historis pada mata pelajaran Sejarah Kebudayaan Islam. Fokus utama kajian ilmiah ini adalah mengeksplorasi penguatan motivasi belajar peserta didik melalui penerapan metode video-based learning. Langkah-langkah penelitian kualitatif deskriptif ini dioperasikan melalui penarikan informan secara purposive sampling yang melibatkan kepala madrasah, guru bidang studi, dan dua belas siswa aktif. Prosedur pengumpulan data primer lapangan dihimpun lewat teknik wawancara mendalam, observasi partisipatif, serta studi dokumentasi, yang selanjutnya dianalisis melalui model interaktif meliputi reduksi data, penyajian, dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa integrasi media audiovisual mampu mentransformasikan atmosfir kelas menjadi lebih dinamis, inklusif, dan responsif. Visualisasi fakta sejarah terbukti andal mengonversi materi abstrak menjadi konkret guna memicu atensi serta rasa percaya diri siswa. Simpulan utama menegaskan bahwa digitalisasi instruksional ini sangat efektif meminimalkan hambatan kognitif meskipun masih terkendala keterbatasan fasilitas proyektor dan pengeras suara. Praktisi madrasah direkomendasikan secara konsisten meningkatkan kompetensi pedagogik digital secara menyeluruh.